2013
DOI: 10.4236/ojn.2013.33042
|View full text |Cite
|
Sign up to set email alerts
|

An ongoing concern: Helping children comprehend death

Abstract: This article addresses the need for anticipatory guidance about death and death education with young children. Children often experience the death of an immediate family member before the age of ten. This number increases if one considers the loss of friends, pets, and other loved ones. However, children experience a death with little or no anticipatory guidance or knowledge about death. Anticipatory guidance can assist the child in having a better understanding of a death when it occurs. Talking about death w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…Integrating death education into school curricula can be an effective approach to pre-emptively supporting children to cope with bereavement. Doing so provides preparatory guidance, which equips children with knowledge, language, and coping strategies that can be drawn upon when a child faces loss (McGuire et al, 2013). Although not currently standard practice in Australian schools (Kennedy et al, 2017), international death education curricula typically incorporate information that facilitates recognition and understanding of grief, language to identify and explain grief, and strategies to cope with grief and related experiences (Dawson et al, 2023;Friesen et al, 2020).…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Integrating death education into school curricula can be an effective approach to pre-emptively supporting children to cope with bereavement. Doing so provides preparatory guidance, which equips children with knowledge, language, and coping strategies that can be drawn upon when a child faces loss (McGuire et al, 2013). Although not currently standard practice in Australian schools (Kennedy et al, 2017), international death education curricula typically incorporate information that facilitates recognition and understanding of grief, language to identify and explain grief, and strategies to cope with grief and related experiences (Dawson et al, 2023;Friesen et al, 2020).…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Higher levels of spirituality and a mature concept of death improve children's emotional well-being and enable them to elaborate on the idea of finitude [49][50][51][52]. Given that children's scores on the TDRS-C scale correlate negatively with the positive dimensions of affectivity (PANAS-C) and prosociality (SDQ) and positively with the negative behavioral dimensions of SDQ, we hypothesize that school-based death education programs, which promote discussion of the existential issues related to spirituality and transcendental dimensions, may promote self-awareness, emotional resilience, compassion, and empathy among children [23,[53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the study also suggested that it is possible to elicit preschool children's understanding of death in a nonthreatening manner. Thus, instead of avoiding discussing the inevitable concept of death with a child, parents and other adults can and should be able to talk about it and help the child understand death (McGuire, McCarthy, & Modrcin, 2013).…”
Section: Discussionmentioning
confidence: 99%